Cognitive Impairment and Brain Imaging Characteristics of Patients with Congenital Cataracts, Facial Dysmorphism, Neuropathy Syndrome - Teodora Chamova; Dora Zlatareva; Margarita Raycheva; Stoyan Bichev; Luba Kalaydjieva; Ivailo Tournev (Behavioural Neurology, 2015)
Congenital cataracts, facial dysmorphism, neuropathy (CCFDN) syndrome is a complex autosomal recessive multisystem disorder. The aim of the current study is to evaluate the degree of cognitive impairment in a cohort of 22 CCFDN patients and its correlation with patients’ age, motor disability, ataxia, and neuroimaging changes. Twenty-two patients with genetically confirmed diagnosis of CCFDN underwent a detailed neurological examination. Verbal and nonverbal intelligence, memory, executive functions, and verbal fluency wеre assessed in all the patients aged 4 to 47 years. Brain magnetic resonance imaging was performed in 20 affected patients. Eighteen affected were classified as having mild intellectual deficit, whereas 4 had borderline intelligence. In all psychometric tests, evaluating different cognitive domains, CCFDN patients had statistically significant lower scores when compared to the healthy control group. All cognitive domains seemed equally affected. The main abnormalities on brain MRI found in 19/20 patients included diffuse cerebral atrophy, enlargement of the lateral ventricles, and focal lesions in the subcortical white matter, different in number and size, consistent with demyelination more pronounced in the older CCFDN patients. The correlation analysis of the structural brain changes and the cognitive impairment found a statistically significant correlation only between the impairment of short-term verbal memory and the MRI changes.